2017
DOI: 10.15389/agrobiology.2017.4.716eng
|View full text |Cite
|
Sign up to set email alerts
|

Vitagene Regulation as a New Strategy to Fight Stresses in Poultry Production

Abstract: A b s t r a c tCommercial poultry production is associated with various stresses leading to decrease of productive and reproductive performance of growing chickens, parent birds and layers. In commercial poultry/animal production, there are four major types of stress: technological, environmental, nutritional and internal stresses. A growing body of evidence indicates that most of the stresses in poultry production at the cellular level are associated with oxidative stress due to excess of free radical product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Therefore, the development of vitagene-regulating nutritional supplements is on the agenda of many commercial companies worldwide. One successful example could be a complex mixture of nutrients including carnitine, betaine, vitamins, minerals, organic acids, etc., which are commercially available for poultry [22,105,[304][305][306]. Indeed, prevention of the detrimental consequences of stressors and improved performance in broilers [22,303], broiler breeders and layers [305,306] using vitagene-activation may, based on references in this review, optimize the antioxidant defence system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the development of vitagene-regulating nutritional supplements is on the agenda of many commercial companies worldwide. One successful example could be a complex mixture of nutrients including carnitine, betaine, vitamins, minerals, organic acids, etc., which are commercially available for poultry [22,105,[304][305][306]. Indeed, prevention of the detrimental consequences of stressors and improved performance in broilers [22,303], broiler breeders and layers [305,306] using vitagene-activation may, based on references in this review, optimize the antioxidant defence system.…”
Section: Discussionmentioning
confidence: 99%
“…One successful example could be a complex mixture of nutrients including carnitine, betaine, vitamins, minerals, organic acids, etc., which are commercially available for poultry [22,105,[304][305][306]. Indeed, prevention of the detrimental consequences of stressors and improved performance in broilers [22,303], broiler breeders and layers [305,306] using vitagene-activation may, based on references in this review, optimize the antioxidant defence system. It seems likely that the vitagene concept of fighting stress could be used for maintenance/improvement of eggshell health, gut health and liver health of modern poultry in conditions under stress (for a review, see Reference [105]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It’s interesting to find that both studies found that heat shock protein, one of the members in vitagene family, expression was increased in the liver of quails suffering a high temperature environment. The vitagene family has been regarded as a promising resolving strategy to fight against detrimental effects caused by oxidative imbalance [ 16 , 86 ] In addition to heat shock proteins, thioredoxins (Trx)/thioredoxin reductase (TrxR) system, SOD, and sirtuins are members that preserve homeostasis in cell, to adapt cells in various stress conditions [ 92 ]. Among those candidates for combating NF-κB in Nrf2-regulated pathway, HO-1 is at the core of Nrf2-mediated NF-κB inhibition, and HO-1 is one of the heat shock family members [ 93 ].…”
Section: Inseparable Issues: Oxidative Stress and Inflammationmentioning
confidence: 99%
“…To analyze the expression of mRNA in the liver and bursa, specific primers were selected [25]. As a reference control, primers were used to amplify the housekeeping gene encoding the ACTB beta-actin protein: F -5´-CTGTGCCCATC-TATGAAGGCTA-3´, R -5´-ATTTCTCTCTCGGCTGTGGTG-3´.…”
Section: Introductionmentioning
confidence: 99%